Evaluation of the Effectiveness of the PMB Team's Services in Supporting the New Student Registration Process at ITB Tuban - Fadhoilus Shofi et.al; Kafka Rozika Mei-V; Faisal Majid; Fima Heryuni Agustin; Widia Selviana Ananda Putri; Ana Rufa Ida; Sita Romadhoni; Ahmad Wildan Habibullah; Nuryani Hera Pramesti; Nurussa'diyah; Rifqi Ainul Ahmadi (STAI AL-HIDAYAT Lasem, 2026)
This study evaluates the effectiveness of the New Student Admission Team services in supporting the student registration process at Institut Teknologi dan Bisnis Tuban. A quantitative survey method was applied by distributing questionnaires to 195 prospective students in the 2025/2026 academic year. The data were analyzed using quantitative descriptive analysis through frequency and percentage calculations. The indicators included staff friendliness, clarity of information, response speed, level of assistance, information media, and ease of registration. The results show that the admission services were effective. A total of 93.3% of respondents rated the team as very friendly, 90.3% stated that the information was very clear, 98% assessed the response as fast and very fast, all respondents felt assisted, and 99% rated the registration process as easy and very easy. The findings indicate that the admission services supported prospective students’ needs, although website optimization, technical information clarity, account verification, and official information media still require improvement.